The tap‐tpg gene pair on the linear plasmid functions to maintain a linear topology of the chromosome in Streptomyces rochei. Issue 5 (24th January 2015) - Nindita, Yosi; Cao, Zhisheng; Yang, Yingjie; Arakawa, Kenji; Shiwa, Yuh; Yoshikawa, Hirofumi; Tagami, Michihira; Lezhava, Alexander; Kinashi, Haruyasu
Summary S treptomyces rochei 7434AN4 carries three linear plasmids, pSLA2‐L (211 kb), pSLA2‐M (113 kb) and pSLA2‐S (18 kb), their complete nucleotide sequences having been determined. Restriction and sequencing analysis revealed that the telomere sequences at both ends of the linear chromosome are identical to each other, are 98.5% identical to the right end sequences of pSLA2‐L and pSLA2‐M up to 3.1 kb from the ends and have homology to those of typical Streptomyces species. Mutant 2‐39, which lost all the three linear plasmids, was found to carry a circularized chromosome. Sequence comparison of the fusion junction and both deletion ends revealed that chromosomal circularization occurred by terminal deletions followed by nonhomologous recombination. Curing of pSLA2‐L from strain 51252, which carries only pSLA2‐L, also resulted in terminal deletions in newly obtained mutants. The tap‐tpg gene pair, which encodes a telomere‐associated protein and a terminal protein for end patching, is located on pSLA2‐L and pSLA2–M but has not hitherto been found on the chromosome. These results led us to the idea that the tap‐tpg of pSLA2‐L or pSLA2‐M functions to maintain a linear chromosome in strain 7434AN4. This hypothesis was finally confirmed by complementation and curing experiments of the tap‐tpg of pSLA2‐M.